An AC-AC High Frequency Pulse Density Modulated Full Bridge Series Resonant Converter for Induction Heating Application - v geetha; V Sivachidambaranathan (International Journal of Electrical and Computer Engineering (IJECE), 2019)
This paper deals with a new AC – AC single stage full bridge series resonant converter for induction heating application. The proposed system is simulated with high power density modulation technique to produce a output power of 1.8Kw.The main feature of the proposed converter is to reduce the total harmonic distortion produced in the output current for the switching frequency of 29Khz.Asymmetrical pulse density modulation technique is proposed to achieve maximum output power with less harmonic content. It is found that the THD of the proposed high power density modulated converter is 13.43%. Here, the validity of the proposed converter for domestic induction heating application is compared and summarized.